ROLE OF CROWDFUNDING IN SUPPORTING SOCIAL ENTREPRENEURSHIP: AN EMPIRICAL STUDY - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana; Devi, Takhelchangbam Brajeshwari (The journal of contemporary issues in business and government, 2021)
Any entrepreneur’s most significant hurdle is obtaining investors and raising cash for their firm. When raising investment funding, social entrepreneurs can face stiff competition from commercial entrepreneurs. As a result, loans and Crowdfunding become the only viable options for ethical entrepreneurs to remain competitive in the market. Thus, it is critical to examine and comprehend the values and consequences of crowd fundraising. Our research examines and surveys the advantages and disadvantages of crowd financing or crowd investing in social entrepreneurship. In hindsight, social entrepreneurs’ failures with equity crowd fundraising reveal many drawbacks, including insufficient public visibility, an indistinctive pool of small investors, inexperienced investors, and often more extraordinary expenses than commercial entrepreneurship. However, there are some benefits, such as increased visibility and marketing of social causes with a powerful message, more accessible access to impact-minded people, increased firm value, and a favorable power balance.